Assessment of climate change impact on viticulture: Economic evaluations and adaptation strategies analysis for the Tuscan wine sector - Iacopo Bernetti; Silvio Menghini; Nicola Marinelli; Sandro Sacchelli; Veronica Alampi Sottini (Wine Economics and Policy, 2012)
Climate change is expected to have a significant impact on various economic sectors (IPCC, 2007) but an especially large one on agriculture because animal and crop growth are heavily influenced by weather conditions during their life cycles. In this paper, a multidisciplinary approach is developed that jointly uses economic and bio-climate models to evaluate the impact of climate change on viticulture in Tuscany (central Italy). Then a model is used to evaluate the likelihood of adoption of various adaptation strategies.
Keywords: 330; Adaptation strategies; Climate change; Wine